Molecular characterisation of Escherichia coli from dead broiler chickens with signs of colibacillosis and ready-to-market chicken meat in the West Bank. - Qabajah, M; Awwad, E; Ashhab, Y (My University, 2014)
1. The aim of this work was to compare a group of virulence-associated characteristics of Escherichia coli isolates from broiler chickens that had died with signs of colibacillosis against E. coli isolates from ready-to-market chicken meat in the West Bank. 2. The isolates were investigated to determine the virulence factor (VF) profile, phylogenetic group and the presence of extended-spectrum beta-lactamase (ESBL). A total of 66 avian pathogenic E. coli (APEC) strains from different affected broiler farms and 21 E. coli isolates from ready-to-market chicken carcasses (hereinafter called meat strains) from 8 slaughter houses were analysed. 3. The overall content of VFs was significantly higher (P < 0.05) among APEC strains, with over 75% of APEC strains having ≥4 VFs, while over 75% of the meat strains had <4 VFs. The VFs iss, astA and iucD were frequently detected in APEC and meat strains, whereas cvi, papC, vat, tsh and irp2 occurred more significantly in APEC strains. Phylogenetic typing showed that 67% of the meat strains belonged to group B2. Phylogroup D was predominant (50%) in the APEC strains. Using double disc diffusion and polymerase chain reaction (PCR), 10.6% of the APEC and 9.5% of the meat strains were determined to be ESBL positive. 4. Our findings show that the VFs papC, vat, irp2 and to a lesser extent tsh and cvi are significantly more prevalent in APEC strains. The results demonstrate that chicken meat can be contaminated with APEC strains (≥4 VF). A significant percentage of the meat strains fall in the B2 group, which is a phylogroup largely associated with human pathogenic ExPEC strains. The results of ESBL screening indicated that broiler chicken products in Palestine represent a potential reservoir of ESBL genes and therefore could be considered a possible public health risk.